Analysis on the impacts of marketing mix towards Malaysian consumer’s satisfaction in purchasing organic pineapples case study at Merlimau Utara, Melaka / Masedayu Othman - Othman, Masedayu (Faculty of Plantation and Agrotechnology, 2019)
Pineapple (Ananas comosus) is tropical fruit that known as a member of Bromeliaceae. Organic pineapple is consumed and planted in Malaysia by using environmental friendly method without use chemical pesticides and fertilizers. However, the market of organic pineapple still not get fully attention in agriculture industry. Organic pineapple would earn a premium price compared to conventional varieties. Thus, the factor of marketing mix was applied to realize the needs and desire of consumers. To achieve high consumer’s satisfaction, we should identify the factors and impacts of marketing mix (product, price, place, and promotion) to develop better strategies for maximizing production whilst increasing profitability of pineapple’s producers. By using organic pineapple as a case study, the objective of this study is to determine the factors of marketing mix that influenced the Malaysian consumer’s satisfaction in purchasing organic pineapple. The study was focused on 5 blocks at Merlimau Utara, Melaka, where 155 randomly respondents were identified to answer the question in the questionnaire. The results obtained have been analysed using Statistical Package for Social Science 22 Version for reliability test, descriptive analysis, and factorial analysis. Four factors were identified by factorial analysis which are product, place, promotion, and price that influenced consumer’s satisfaction. Kaiser-Meyer-Olkin Measure was 0.692 indicated that the value was acceptable which means factor analysis was appropriate for the data. Factorial analysis result shows that product was the most dominant attribute which represented by four factors that eigenvalues more than 1, factor 1 (comparison), factor 2 (commercial fruit), factor 3 (advantageous), factor 4 (advantages to health and environment). It was 46.72 % of the total variance explained by the factor. The study recommended on the improvement on services should be highlighted, research and development related on pineapple industry should give fully attention by farmers and government.